If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -1x = 2(2 + -1x) 4 + -1x = (2 * 2 + -1x * 2) 4 + -1x = (4 + -2x) Add '-4' to each side of the equation. 4 + -4 + -1x = 4 + -4 + -2x Combine like terms: 4 + -4 = 0 0 + -1x = 4 + -4 + -2x -1x = 4 + -4 + -2x Combine like terms: 4 + -4 = 0 -1x = 0 + -2x -1x = -2x Solving -1x = -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -1x + 2x = -2x + 2x Combine like terms: -1x + 2x = 1x 1x = -2x + 2x Combine like terms: -2x + 2x = 0 1x = 0 Divide each side by '1'. x = 0 Simplifying x = 0
| 5(X-4)=2(X+8) | | 9-6x=-4(4-2x) | | 0.55[f-32]=25 | | (7x+5)=0 | | 24x^4+16x^2-8=0 | | sqrt64/25 | | 4x=3(2+1x) | | 30+25x=105 | | x^2-12x+48=4 | | -3x+14=x-10 | | 12x+3y-(4x-2y)= | | M=10+-1m | | Cos(6x)+cos(4x)=o | | (1-3x)=0 | | 2x+5x=10x+60 | | 2A+10X^4C=0 | | 12x-3y-2(4x+y)= | | 2x-20=80 | | 7x+8y+3(2x+4y)= | | 5a+7a-6b-3a= | | 2(2n-3)=2n-2(n-1) | | m=4+m | | -5(-2x+3)= | | 7x-3y+9x-2y= | | Dx+9y=27 | | 5/8(x-7)=10 | | logv[12](x)+logv[12](11x-1)=1 | | 12x+5y=8400 | | 12x=6x+20-8 | | 5p+7s+4p-3s= | | 4x-32=9x+17 | | 15m^2-5m^2=30m+11m |